Digitalization Strategies and Innovation in Traditional Cuisine: Efforts to Enhance the Competitiveness of Nasi Jamblang in the Creative Economy Era - Arya Yudistira; Ahmad Siroj J; Urfi Arham; Rifki Alpauji; Siska Reina Zuniar; Refa Husni Hanifah; Nurul Hidayah Muhammad; Nur Fadilah; Fajar Wirawardana; Fadly Nurfadila; Itto Turyandi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of digitalization strategies and innovation practices in strengthening the competitiveness of Nasi Jamblang as a traditional culinary product within the contemporary creative economy era. The research employed an empirical qualitative design using descriptive analysis based on observations, in depth interviews, and documentation collected from Nasi Jamblang culinary enterprises, including Mang Darma restaurant in Bandung. The findings indicate that digital adaptation has contributed to broader market accessibility and improved business visibility, although the implementation remains uneven due to limited technological capability and managerial experience among several business actors. Innovation practices were reflected through product diversification, adaptive service improvement, branding enhancement, and operational transformation that maintained traditional culinary authenticity while responding to changing market demands. The study also reveals that cultural sustainability plays a crucial role in preserving Nasi Jamblang as a socio cultural identity and creative economy asset connected to gastronomic tourism and regional development. The integration of innovation, cultural preservation, and adaptive entrepreneurship strengthens the long term sustainability and competitiveness of traditional cuisine within increasingly dynamic economic environments.